Dietary fiber consumption in an adult population - Mattos, Lúcia Leal de (2000)
OBJECTIVE: The dietary fiber has emerged as a leading dietary factor in the prevention and treatment of chronic diseases. I was estimated the average consumption of total dietary fiber (DF), insoluble fiber (IF) and soluble fiber (SF) in the meals of both sex adults from the town of Cotia, a metropolitan area in S. Paulo State, Brazil. METHODS: A population sample of Cotia country, S. Paulo (Brazil), consisted of 559 adults older than 20 years old, was studied. Food consumption was assessed by the dietary history habits. The amount of dietary fiber in each meal (breakfast, lunch and diner) was estimated by the serving size. The foods were classified according to their fiber content in Very High (7 g or more), High (4.5 to 6.9), Moderate (2.4 to 4.4) and Low (